Hydrochemical aspects of high-temperature aquifer storage in carbonaceous aquifers: evaluation of a field study - Martina Ueckert (Geothermal Energy, 2019)
Abstract Aquifer thermal energy storage systems in the sediments of the Upper Jurassic in the north-eastern part of the Bavarian Molasse Basin seem to be feasible in terms of the hydrogeological and hydrochemical setting. This study presents unique results from the first large-scale high-temperature heat storage test in these sediments and a hydrogeochemical model based and validated with the field data. The test was run in a single well setting with five injection and production cycles and temperatures from 65 to 110 °C. The flow rates were 15 L/s. Due to the very high transmissivity, mixing and density–driven flow have been observed and confirmed by hydrochemical analyses. Mixing was quantified using the natural contrast of the sodium ion concentrations as a natural tracer. Using the mixing ratios, a deduction of the effects of mixing on the temperature of the produced water was possible and a correction was applied to the recovered energy. The temperatures of the produced water show that 48% of the injected energy was recovered during the field test and the remaining energy is “charging” the aquifer. A kinetic hydrogeochemical model including 1D-transport was developed with PhreeqC to quantify the reactions in the reservoir and calibrated with the hydrochemical data of the first and second phase of the field test. The other three phases of the field test were used for validation. Model and measurement data were in excellent agreement and show significant dissolution of carbonates which can be attributed to an undersaturation of the water as it equilibrates with the matrix at lower temperatures. Based on field data from the single well test and the calibrated model, the operation of an ATES system was designed and simulated. Model results indicate that a doublet setting for ATES cannot be operated for more than a few cycles, regardless of the conditioning methods. In a triplet system, however, the time frame for successful operation can be extended to decades.